Residential indoor exposure to fine and ultrafine particulate air pollution in association with blood pressure and subclinical central haemodynamic markers of cardiovascular risk among healthy adults living in Perth, Western Australia - Gilbey, Suzanne; Reid, Christopher M; Zhao, Yun; Soares, Mario J; Huxley, Rachel R; Rumchev, Krassi B (Springer Nature, 2022)
Despite that large percentages of individual daily time is spent in the home, few studies have examined the relationship between indoor particulate matter (PM) exposure in residential settings with subclinical indicators of cardiovascular risk. This cross-sectional study investigated associations between exposure to fine (PM2.5) and ultrafine (UFP) PM in domestic indoor environments, with central blood pressure (BP) and component BP measures (pulse pressure, augmented pressure [AP], augmentation index [AIx], mean arterial pressure, pulse wave velocity [PWV]) in 40 non-smoking, otherwise healthy adults (58% women) living in Perth, Western Australia. Overall, in adjusted models, an interquartile range (IQR) increase in PM2.5 was associated with a 3.2 mmHg (95% confidence interval [CI]: 0.99, 5.45) higher diastolic BP, and a 1.8 mmHg lower AP (95%CI: − 3.63, − 0.01) and 0.4 m/s PWV (95%CI: − 0.80, − 0.08), respectively. For the UFP fraction, an IQR increase was associated with a 5.2% higher AIx (95%CI: 0.51, 9.97) and a 0.6 m/s lower PWV (95%CI: − 1.00, − 0.11).